2020
DOI: 10.1149/1945-7111/ab7d43
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Ni-Doped ZnO Nanorod Arrays for UV Photodetector Application

Abstract: In this work, the structure morphologies, lattices, and optical properties of zinc oxide (ZnO) nanorods (NRs) with various amounts of nickel (Ni) dopants were investigated and explored. The 100 nm ZnO seed layer was grown on the Corning glass substrate by the radio frequency (RF) magnetron sputtering technique, and the chemical bath deposition (CBD) method was used to grow NR arrays. It was found that the Ni concentration of the sample is 1.06 at% by EDX spectra examination. All the NRs exhibited a hexagonal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…The physics mechanism for high sensitivity and recovery speed can be explained by the photon-induced oxygen desorption from the surface of the ZnO NWs which has been described elsewhere [34]. Cheng et al reported an individual ZnO NW-based SBUV-VIS-NIR photodetector with MSM structure and two back-to-back Schottky junctions [101]. However, the broad-spectral-response property was not explained by the photon-induced oxygen desorption.…”
Section: A Conversional Zno Nws/nrs-based Ultraviolet Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physics mechanism for high sensitivity and recovery speed can be explained by the photon-induced oxygen desorption from the surface of the ZnO NWs which has been described elsewhere [34]. Cheng et al reported an individual ZnO NW-based SBUV-VIS-NIR photodetector with MSM structure and two back-to-back Schottky junctions [101]. However, the broad-spectral-response property was not explained by the photon-induced oxygen desorption.…”
Section: A Conversional Zno Nws/nrs-based Ultraviolet Photodetectorsmentioning
confidence: 99%
“…The concentration of free electrons in the conduction band was enhanced after Fe-doping, resulting in increased responsivity. Furthermore, the hole-trapping mechanism through oxygen adsorption and desorption in Fe-doped ZnO NRs can also improve the responsivity of the prepared photodetector [101], [102]. Jayalakshmi reported the performance of a plasmonic nickel (Ni) nanoparticles (NPs)-decorated ZnO NRs-based UV photodetector.…”
Section: A Conversional Zno Nws/nrs-based Ultraviolet Photodetectorsmentioning
confidence: 99%
“…ZnO is a good crystallinity material. It has a hexagonal structure, and the lattice constants are a = 3:24 -3:26 Å and c = 5:13 -5:43 Å [7][8][9]. In addition, the lowest surface free energy of ZnO thin films lies on the (002) plane, and a good c-axis orientation can be obtained at a low temperature when ZnO thin films are grown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has a hexagonal structure, and the properties of lattice constants are a = 3.24–3.26 Å and c = 5.13–5.43 Å [ 9 , 10 ]. ZnO has attracted tremendous and wide interest in different fields, such as field-emission displays (FEDs), PDs, gas sensors, and pH sensors [ 11 , 12 , 13 , 14 ]. Therefore, ZnO has gradually become a promising material for various applications in modern times.…”
Section: Introductionmentioning
confidence: 99%